Efficacy of a house dust mite sublingual immunotherapy tablet as add-on dupilumab in asthma with rhinitis - Makoto Hoshino; Kenta Akitsu; Kengo Kubota; Junichi Ohtawa (Allergology International, 2022)
Background: HDM SLIT is one of the disease-modifying treatment for allergic asthma, and has demonstrated efficacy in clinical trials. Dupilumab, blocks IL-4 and IL-13 signaling, key drivers of type 2 inflammation, and is approved for patients with uncontrolled, moderate-to-severe asthma. The aim of this study was to evaluate outcomes after HDM SLIT initiation in asthma with rhinitis not optimally controlled with dupilumab in a real-world setting. Methods: At baseline and 48 weeks after treatment, asthma control questionnaire (ACQ)-5, asthma quality of life questionnaire (AQLQ) and rhinoconjunctivitis quality of life questionnaire (RQLQ) were assessed. Spirometry, type 2 inflammatory biomarkers and quantitative computed tomographic parameters of airway remodeling were also collected. Results: Of 47 patients received HDM SLIT and 41 completed the study. Combined HDM SLIT and dupilumab improved ACQ-5 (p < 0.05), AQLQ (p < 0.05), RQLQ (p < 0.05), and increased lung function and reduced FeNO (p < 0.05) and airway percentage wall area, and wall thickness (each, p < 0.05). The change in ACQ-5 and AQLQ score correlated with both changes in FeNO and FEV1 percent predicted. Multiple regression analysis showed that the change in FEV1 percent predicted was independent factor for improvement of AQLQ (r2 = 0.510, p = 0.012). Based on ROC analysis for predicting SLIT responders, the baseline area under the curves in serum HDM specific-IgE, total IgE and FEV1 percent predicted were high (>0.8). Conclusions: These results support the benefits of adding HDM SLIT to pharmacotherapy plus dupilumab in uncontrolled asthma with rhinitis.